BLOOD TRANSFUSION IN THE MANAGEMENT OF THOSE INJURED: CERTAIN ORGANIZATIONAL PROBLEMS - S. V. Nedomolkin; V. V. Suvorov; S. A. Smirnov; V. Yu. Markevich; I. M. Samokhvalov; B. N. Bogomolov; S. V. Gavrilin; D. P. Meshakov; V. I. Badalov; A. V. Turtanov (Вестник анестезиологии и реаниматологии)
The tactics of blood transfusion therapy provides a significant impact on the course of wound disease but only in those with acute massive blood loss of the extremely severe degree. A proper use of blood transfusions in the post-shock period results in faster relief of the severity and reduces the risk to develop severe sepsis and acute respiratory distress syndrome. One of the most crucial organizational problems in blood transfusion is the issue of blood donation being especially critical in treatment of those with severe traumas since they often require blood transfusions including massive ones. The existing regulatory documents containing indicators and procedures for using blood transfusion media in those with severe traumas are often contradictory and require certain amendments.